CONTROL OF STRESSED STATE OF UNDERGROUND STRUCTURES - Shalaurov V.A.; Frejdin A.M.; Bykadorov A.I. (My University, 2001)
Opportunities for controlling the stressed state of underground structures have been considered. It has been shown that method of oriented fluid break is efficient technique of control. Physical and mathematical models of oriented fluid break as method of stress redistribution in zone influenced by mine working have been developed. Technologies schemes of mining the deposits have been shown which make it possible to unload interchamber pillars and barrier pillars, edge zones of exploited seams and ore bodies. Experiments have been performed with the use of optically sensitive model material of SD-8 type.